A Dynamic Model for Fishery Resource with Reserve Area and Taxation - Hai-Feng Huo; Hui-Min Jiang; Xin-You Meng (Journal of Applied Mathematics)
The present paper deals with a dynamic reaction model of a fishery. The dynamics of a fishery resource system in an aquatic environment consists of two zones: a free fishing zone and a reserve zone. To protect fish population from over exploitation, a control instrument tax is imposed. The existence of its steady states and their stability are studied. The optimal harvest policy is discussed next with the help of Pontryagin's maximum principle. Our theoretical results are confirmed by numerical simulation.